An Analysis Of The American Slang Used In 'The Fast and Furious X' Movie - Sitorus, Agustina; Tampubolon, Sahlan; Napitupulu, Fenty Debora (Jurnal Kajian Ilmu Pendidikan (JKIP), 2024)
Languange is a circumstance that allows content to differ from one place to another since it is tied to the social ties and culture of the specific community that speaks it. This study aims to find out the kinds of slang, to find out the kinds of slang are dominantly and to find out the interpretations in “The Fast ad Furious X” Movie. The writer uses qualitative descriptive research and the research design is observational analysis. Where the writer describes one by one word of slang languange from the movie. The writer founded four kinds of slang, they are society slang, public house slang, slang in commerce and slang in medicine. From a total of 29 slang words in the movie, society slang (68.97%), public house slang (24.13%), slang in commerce (3.45%) and slang in medicine (3.45%). This shows that the dominant in the movie is society slang. The slang words are kill, what’s happening, shit, gonna, love, goddamn, why the hell, damn, holy shit, awesome, wow, go ahead, bravo, bad, bullshit, awkward, as soon as possible, gotcha, kinda and amazing. The slang words included in the society slang. According to the writer, it can be assumed that the society slang because this common words that often used in daily speech and is associated with society based on the theory of slang by Eric Partridge.